Integrating AI in Phyllanthus emblica Review – A New Era in Phytomedicine Discovery and Development - Samrudhi Kailas Ghorpade,; Dr. Sachin B. Somwanshi, (Asian Journal of Pharmaceutical Research and Development, 2026)
Phytomedicine derived from medicinal plants such as Phyllanthus emblica (Amla) offers a wide range of health benefits due to its rich composition of bioactive compounds. This review explores the current knowledge on the phytochemical profile and therapeutic potential of P. emblica. The plant is well recognized for its antioxidant, anti-inflammatory, antimicrobial, and hepatoprotective properties, which are largely attributed to its high content of vitamin C, polyphenols, flavonoids, and tannins. We summarize key findings from recent research, including advances in the characterization of its phytochemicals, genomic and metabolomic studies, and pharmacological evaluations. Special emphasis is placed on the mechanisms underlying its medicinal effects and its applications in traditional and modern healthcare. The review also discusses the challenges related to standardization, quality control, and sustainable use of P. emblica resources. Finally, we outline future perspectives for developing evidence-based herbal formulations and nutraceuticals derived from this versatile medicinal plant. By integrating traditional knowledge with modern scientific approaches, researchers can continue to uncover new therapeutic insights from P. emblica and promote its use in global health care.